MEASURING ENGLISH LANGUAGE TEACHER CANDIDATES’ INTERCULTURAL SENSITIVITY: A KEY ELEMENT TO FOSTER INTERCULTURAL COMMUNICATIVE COMPETENCE - Çetin Köroğlu, Zeynep (International Online Journal of Education and Teaching, 2016)
A multicultural and global society makes intercultural communication an indispensable part of communication. As an affective dimension of intercultural communicative competence, intercultural sensitivity has drawn the attention of scholars throughout the past years. However, there is still a misperception about intercultural sensitivity with other cognitive, affective and behavioral domains of intercultural communication such as intercultural awareness, intercultural adroitness and intercultural communicative competence. Important scholars in the field define intercultural sensitive persons as those who are conscious in their interactions and accept interlocutors’ ideas without judgment of their personal complexity. In this angle, English language teachers’ sensitivity towards other cultures has significant meaning to make language learners better foreign language learners and speakers. Thus, the current study aims to investigate English Language Teacher candidates’ intercultural sensitivity level. In this study, ISS (intercultural sensitivity scale, Chen and Starosta, 2000) is used to measure the results of the 61 student teachers who participated in the study. Participants’ intercultural sensitivity levels are analyzed in SPSS due to interaction engagement, respect for cultural differences, interaction confidence, enjoyment and attentiveness. The results show that English language teacher candidates enjoy interacting with people from other cultures and they are sensitive towards cultural differences and complexities. Keywords: Intercultural Communication, Intercultural Sensitivity, Culture, English Language Teachers.